Differences in lower leg kinetic of soccer instep kicking between female and male players - Iitake, T.; Hioki, M.; Takahashi, H.; Nunome, H. (Sports Biomechanics, 2022)
We aimed to clarify the difference in lower leg segment kinetics of soccer instep kicking between female and male players. Instep kicking motions of seven female and seven male university soccer players were captured at 500 Hz. Lower leg angular velocity, knee joint moment and the interaction moment acting on the lower leg were calculated. Discrete variables were compared using two sample-t-test, and statistical parametric mapping were used to compare the time-series changes between the two groups. Although female players maintained a comparable magnitude of lower leg angular velocity, they exhibited significantly lower knee extension moment in the latter part of kicking and significantly smaller forward angular impulse due to that moment. In contrast, female players were found to have a comparable magnitude of angular impulse due to forward component of interaction moment to that of male players. Eventually, female players come to have significantly larger ratio of angular impulses (forward interaction moment/knee extension moment) than male players. It can be considered that the forward component of interaction moment acting on the lower leg of female players may compensate their reduced exertion of knee extension moment, thereby achieving a comparable lower leg angular velocity to that of male players.